Castlemanova choroba - neobvyklý nález při operaci tumoru retroperitonea u mladého nemocného - Fichtl, J; Třeška, V; Vodička, J; Šulc, R; Hes, O; Tupý, R (Rozhledy v chirurgii, 2016)
UNLABELLED: Castleman disease is rare diagnosis. It was first mentioned in literature in 1954 by doctor Castleman and Lown. It is rare sickness which primary affects lymfatic nodes. There are four histo-morfologic subtypes and two clinic manifestations (uni and mulicentric). Comon clinical picture is simple lymfadenopathy of neck, medistinal a retroperitonal lymfatic nodes. Signs of this disease are heterogenic and depend on histological subtype. Also prognosis depends on type of illness. It should take place as benign diagnosis (unicentric form) but also can be potencionally malignant form which shlould exacerbate to malignant lymfoproliferation (multicentric form). Authors present the case of 29 years old men with clinical manifestation (jundice, intermitent bowel obstruction) of lagre retroperitoneal tumor in subhepatal localization. The treatment was radical surgical extirpation, surgery was without complications. Definitive histological diagnosis was confirmed as hyaline-vascular type of Castleman disease. Because the patient´s clinical form was multicentric, he is now undergoing adjuvant oncological treatment. KEY WORDS: Castleman disease reproperitoneal tumor.
Keywords: Retroperitoneal Neoplasms; dospělí; mužské pohlaví; prognóza; hyperplazie velkých lymfatických uzlin; lidé; Adult; Castleman Disease; Diagnosis, Differential; Male; Intestinal Obstruction; diferenciální diagnóza; žloutenka; retroperitoneální nádory; Jaundice; Humans; střevní obstrukce; Prognosis